Pasar Lakessi: Antara Persaingan dan Etika - Anjasari, Armita; Muhammad Kamal Zubair; Muhammad Satar; Muzdalifah Muhammadun; Adhitia Pahlawan Putra (Al Rikaz: Jurnal Ekonomi Syariah, 2023)
This article aims to reveal the relationship between ethics and competition in the Lakessi Market and identify what business strategies have been implemented as well as construct competitive strategies for traders to prioritize Islamic business ethics. This research method uses qualitative research methods. This type of research is field research (Field Research). Data collection techniques used are observation, interviews, and documentation. The technique used in analyzing the data is by means of data reduction, data display and drawing conclusions. The results of this study indicate that the strategy of competitive advantage for food traders that occurs in the Lakessi Market has objects in the competitive advantage strategy, namely: prices that are suitable for buyers, quality products and good packaging and service. However, in being fair, there are still basic food sellers who cheat in measuring quantities that can harm the buyer. Then in the review of Islamic business ethics on the strategy of competitive advantage for food traders in the Lakessi Market includes 5 principles, namely monotheism, justice, truth, free will and responsibility. From this principle, most of the trading activities in a competitive advantage strategy carried out by basic food traders are in accordance with Islamic business ethics, although there are still some basic food traders who practice unfair trading methods that conflict with Islamic business ethics, namely cheating in terms of weighing scales. to the detriment of the buyer.